2016
DOI: 10.1021/acssuschemeng.6b00935
|View full text |Cite
|
Sign up to set email alerts
|

Outright Green Synthesis of Fluorescent Carbon Dots from Eutrophic Algal Blooms for In Vitro Imaging

Abstract: Carbon dots (CDs) synthesized from biological sources have attracted much interest in bioimaging and biomedical applications due to their excellent biocompatibility, and thus, a facile synthesis of CDs with high fluorescence quantum yield (QY) is requisite for practical applications. In this work, we report a simple, rapid, and green approach to synthesize photoluminescent CDs using eutrophic algal blooms as the carbon source. This method offers a possibility for large scale production of highly luminescent CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(101 citation statements)
references
References 38 publications
4
97
0
Order By: Relevance
“…The fluorescence quantum yield of the prepared BCDs was 5.4%. In addition, the preparation of BCDs by microwave method is also rose, eutrophic algae and the like. It has been reported that using rose as carbon source, BCD was prepared by simple and effective microwave method.…”
Section: Methods For the Synthesis Of Bcdsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence quantum yield of the prepared BCDs was 5.4%. In addition, the preparation of BCDs by microwave method is also rose, eutrophic algae and the like. It has been reported that using rose as carbon source, BCD was prepared by simple and effective microwave method.…”
Section: Methods For the Synthesis Of Bcdsmentioning
confidence: 99%
“…The BCDs emit blue fluorescence with a QY of 13.45% and exhibit a size distribution from 4 to 6 nm without agglomeration. A simple, rapid, and green method for the synthesis of photoluminescent BCDs from eutrophic algae by microwave has been reported. The BCDs were prepared to have an average particle diameter of 8 nm and a fluorescence QY of 13%.…”
Section: Methods For the Synthesis Of Bcdsmentioning
confidence: 99%
“…Here, I D /I G is found to be 1.27, indicating the presence of high defect density which helps to enhance the electro‐catalytic activity of CQD towards hydrazine detection. This high defect density also serves as a confirmation that the as‐synthesized material was Carbon Quantum dots (CQD) rather than Graphene Quantum dots . XPS analysis can be found in SI.…”
Section: Figurementioning
confidence: 99%
“…Phosphorous (P) is essential for maintaining profitable crop production [12,13]. However, it might cause eutrophication in lakes and ponds, thereby destroying the ecosystem [14]. In recent years, attention for biochar has increased because of its absorption abilities [15,16].…”
Section: Introductionmentioning
confidence: 99%